Impacts of solar variability on distribution networks performance - Annathurai, Vinodh; Gan, Chin Kim; Ab Ghani, Mohd Ruddin; Baharin, Kyairul Azmi (Research India Publications, 2017)
The Distributed Generation (DG) and renewable energy resources have been identified as one of the promising ways to sustain the future energy needs. However, most of the energy produced by DG and renewable energy, particularly the Photovoltaic (PV) system is intermittent in nature and often fluctuates. In this regard, this paper utilizes the Malaysian Reference Network (RN) that aims to analyse the impact of PV integration at the medium voltage (MV) network under solar variability conditions. More precisely, the network losses and voltage issues were evaluated on various PV variability indices (VI). This case study has been carried out in the urban and rural MV networks. Various PV variability days have been considered in the case study. The results show that fluctuation of network losses and voltage could pose a concern for PV integration on the MV network.